Borrowing the Womb of a Second Wife: An Indonesian Legal Perspective - Br. Sibuea, Masri Rumita (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The purpose of marriage is to form a happy and eternal family, one way to achieve this is to have offspring that come from the husband and wife's own gamete cells. One of the obstacles faced by a married couple is when the wife is unable to conceive and give birth to a child due to a problem with the wife's uterus. One way that can be taken to overcome this obstacle is through surrogacy, namely the husband and wife rent another woman's uterus as a surrogate mother to conceive and give birth to their fetus in exchange for a sum of money. Currently, renting another woman's uterus without a valid marriage bond is prohibited in Indonesia, making this act illegal. Renting a uterus to be valid in the eyes of the law must be based on a valid marriage, namely by marrying a surrogate mother. The problem is how to arrange borrowing the womb of a second wife based on Law Number 16 of 2019 concerning Amendments to Law Number 1 of 2019 concerning Marriage and the legal status of children born from the first wife by the second wife based on the Civil Code. The type of research used in this study is normative library research. The type of data used is secondary data. Drawing conclusions is done by starting from general things to then be applied to specific things. The purpose of a husband's marriage with more than one wife because the wife cannot bear children changes the term rent to borrow. The marriage law has accommodated this, where the court grants permission to a husband who will have more than one wife if one of the requirements is that the wife cannot bear children. A husband who applies to the court to have more than one wife must meet the requirements, namely obtaining approval from the wife; certainty that the husband is able to guarantee the necessities of life for his wife and children; guarantee that the husband will be fair to his wife and children. The legal status of a child can be determined from the marital status of the child's parents or the qualification of not being related by blood to the parents as determined by the court. The legal status of a child born to a second wife for a first wife based on the Civil Code (KUHPer) is determined by whose the gamete belongs. The KUHPer states that a legitimate child is a child who is born or raised during a marriage, has a husband as his father, so if the gametes come from the husband and first wife, then the legal status of the child is a legitimate child of the first wife, because the child born is not genetically related to the surrogate mother because it does not use the surrogate mother's ovum cells. If the gamete involves the surrogate mother's ovum cells, then the child is the legitimate child of the second wife.